Fitness in mathematics curriculum. - Tabash Blanco, Nayibe (2011)
The issue about curriculum reform is of great interest to education professionals. The challenge of achieving learning that address student individuality, highlights the need for such learning to be meaningful, itnecessarily implies contextualization processes and teachers capable of developing a curriculumcreatively and assuming the role of researchers intheir daily actions.This article tries to present howCurricula that can be seen from an institutional and individual perspective.